Education-Based Family Empowerment in Diabetic Foot Ulcer Early Detection Using Ipswich Touch Test of Knowledge and Skills - Aan Dwi Sentana; Ni Putu Sumartini; Mardiatun Mardiatun; Agus Supinganto (Jurnal Kesehatan Prima, 2023)
Identifying patients with diabetes mellitus who experience an impaired sensation that ultimately causes Diabetic Foot Ulcer (DFU) is a necessary action. One of the efforts to prevent diabetic foot is to identify, which can be done by family members of the patient at home, but this has not been done. The aim is to determine the effect of education-based family empowerment in the early detection of Diabetic Foot Ulcers using the Ipswich Touch Test on knowledge and skills at the Mataram City Health Center. The design used a pre-experimental design with a pre-post one-group test. The sample was 45 respondents given family empowerment interventions through coaching in educational programs four times a week for two weeks. The results of family knowledge before being given the intervention were mostly lacking, as many as 36 people (86.7%), while after being given the intervention, all respondents got good knowledge, as many as 45 people (100% and p-value = 0.000 < = 0.005 coaching with p = 0.000 and skills All of the skill families before being given the intervention had poor skills as many as 45 people (100%) and after being given the intervention all respondents got good skills as many as 45 people (100%) p = 0.000 < = 0.005. So it can be concluded that education-based family empowerment in early detection of diabetic foot ulcers using the Ipswich touch test on knowledge and skills.